CONDITIONS OF CONFORMITY AMONG HADITHS: AN ANALYTICAL STUDY OF IMAM AL-TAHAWI’S PERSPECTIVE (Al-Aasar, 2025)
Certain Hadiths appear to be mutually contradictory. This perceived conflict is typically resolved through abrogation (naskh), preference (tarjih), or reconciliation/conformity (jam’ wa tatbiq). This research paper focuses on the analytical study of tatbiq (conformity) as a method for resolving such contradictions, specifically through the lens of Imam al-Tahawi’s scholarship. Using a descriptive and analytical methodology, this study examines examples from al-Tahawi’s primary works. It further incorporates the viewpoints of other experts in Uloom al-Hadith (Hadith Sciences). The study concludes that al-Tahawi effectively utilized the principle of conformity to resolve discrepancies, aligning with the wider scholarly community on several conditions while maintaining distinct methodological nuances, particularly regarding his flexibility on the equality of narrations and his prioritization of contextualization over abrogation